Manual acupuncture versus sham acupuncture and usual care for prophylaxis of episodic migraine without aura: multicentre, randomised clinical trial. (25th March 2020) - Xu, Shabei; Yu, Lingling; Luo, Xiang; Wang, Minghuan; Chen, Guohua; Zhang, Qing; Liu, Wenhua; Zhou, Zhongyu; Song, Jinhui; Jing, Huitao; Huang, Guangying; Liang, Fengxia; et al.
Abstract: Objective: To assess the efficacy of manual acupuncture as prophylactic treatment for acupuncture naive patients with episodic migraine without aura. Design: Multicentre, randomised, controlled clinical trial with blinded participants, outcome assessment, and statistician. Setting: Seven hospitals in China, 5 June 2016 to 15 November 2018. Participants: 150 acupuncture naive patients with episodic migraine without aura. Interventions: 20 sessions of manual acupuncture at true acupuncture points plus usual care, 20 sessions of non-penetrating sham acupuncture at heterosegmental non-acupuncture points plus usual care, or usual care alone over 8 weeks. Main outcome measures: Change in migraine days and migraine attacks per four weeks during weeks 1-20 after randomisation compared with baseline (four weeks before randomisation). Results: Among 150 randomised patients (mean age 36.5 (SD 11.4) years; 123 (82%) women), 147 were included in the full analysis set. Compared with sham acupuncture, manual acupuncture resulted in a significantly greater reduction in migraine days at weeks 13 to 20 and a significantly greater reduction in migraine attacks at weeks 17 to 20. The reduction in mean number of migraine days was 3.5 (SD 2.5) for manual versus 2.4 (3.4) for sham (adjusted difference −1.4, 95% confidence interval −2.4 to −0.3; P=0.005) at weeks 13 to 16 and 3.9 (3.0) for manual versus 2.2 (3.2) for sham (adjusted difference −2.1, −2.9 to −1.2; P<0.001) at weeks 17 to 20. At weeks 17 to 20, the reduction in mean number of attacks was 2.3 (1.7) for manual versus 1.6 (2.5) for sham (adjusted difference −1.0, −1.5 to −0.5; P<0.001). No severe adverse events were reported. No significant difference was seen in the proportion of patients perceiving needle penetration between manual acupuncture and sham acupuncture (79% v 75%; P=0.891). Conclusions: Twenty sessions of manual acupuncture was superior to sham acupuncture and usual care for the prophylaxis of episodic migraine without aura. These results support the use of manual acupuncture in patients who are reluctant to use prophylactic drugs or when prophylactic drugs are ineffective, and it should be considered in future guidelines. Trial registration: Clinicaltrials.gov NCT02765581 .